2018
DOI: 10.15406/japlr.2018.07.00246
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal fabrication and characterization of ZnO/Fe2O3 heterojunction devices for hydrogen production

Abstract: ZnO/Fe 2 O 3 heterojunction were prepared by sequentially depositing iron oxide α-Fe 2 O 3 and zinc oxide ZnO films on FTO (SnO 2 :F) substrates. The α-Fe 2 O 3 and ZnO films and the α-Fe 2 O 3 / ZnO heterojunction were characterized by Field Emission Scanning Electron Microscopy (FESEM), Energy-Dispersive X-ray spectroscopy (EDX), and X-Ray Diffraction (XRD). Pure crystalline ZnO films were hydrothermally deposited on α-Fe 2 O 3 films and the process parameters were as follows: hydrothermal time, 4h; temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…The overall PEC reaction can be represented as 2H 2 O / 2H 2 + O 2 (DE ¼ À1.23 V/RHE). 21 Since H 2 O oxidation is the rate-limiting reaction in the overall PEC water splitting, the design of an efficient photoanode is an important barrier to overcome to perform this reaction. 22 For efficient PEC water splitting, ZnO is a prominent semiconductor owing to its low cost and high catalytic efficiency.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The overall PEC reaction can be represented as 2H 2 O / 2H 2 + O 2 (DE ¼ À1.23 V/RHE). 21 Since H 2 O oxidation is the rate-limiting reaction in the overall PEC water splitting, the design of an efficient photoanode is an important barrier to overcome to perform this reaction. 22 For efficient PEC water splitting, ZnO is a prominent semiconductor owing to its low cost and high catalytic efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…They got maximum photoconversion efficiency (2.7%) under solar irradiation of 100 mW cm À2 for PEC hydrogen generation using the electrode grown for 3 h. The maximum hydrogen rate was 22 mL cm À2 aer 1 h exposure. Moreover, Bouhjar et al 21,28 showed that the PEC efficiency of the hydrothermally grown a-Fe 2 O 3 /ZnO heterojunction is higher than that of FTO/a-Fe 2 O 3 and FTO/ZnO. Furthermore, Kim et al 29 introduced complex co-sensitized ZnO/WO x heterostructures for efficient visible light absorption and PEC hydrogen production.…”
Section: Introductionmentioning
confidence: 99%
“…The correlation between temperature and composition of nitrogen plasma can be carried out in accordance with the kinetic model proposed in [10]. It can be estimated that during the transition from mode M to mode A with an increase in the average mass temperature from 4÷6 to 8÷10 kK, the molecular component of nitrogen plasma significantly decreases.…”
Section: Hydrophobicity Of Tiomentioning
confidence: 81%
“…In particular, the Teflon-AF grade (DuPont, Wilmington, DE, USA) used in [9] has a decomposition temperature of 360 • C. Complex and expensive equipment is required to obtain a polymer coating with good adhesion to the sample surface and thermal stability. On the other hand, complexes of materials possessing high functionality, in particular, ZnO/Au, ZnO/Fe 2 O 3 , are effective selective gas sensors and photocatalysts [10]. In this work, it is proposed to coat ZnO with non-polar inorganic materials with high heat resistance and good adhesion to ZnO, for example Au and Fe 2 O 3, to increase superhydrophobicity.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the overall enhancement in the photocurrent density can be also attributed to the improved light harvesting ability of the material itself, coming from the adequate band‐edge alignment of the two semiconductors involved in the formation of the heterostructure. [ 154 ]…”
Section: Junctionsmentioning
confidence: 99%